Pengaruh Media Blog terhadap Peningkatan Semangat Belajar Bahasa Arab Siswa Madrasah Aliyah Wali Songo Sebaung Gending Probolinggo - Umar Manshur; Isnol Khotimah; Imarotus Sholihah (PALAPA, 2022)
This research aims to describe the Influence of Media Blogs on Improving the Spirit of Learning Arabic students of class XI MAK Madrasah Aliyah Wali Songo. Because learning media plays an important role in learning Arabic as a means to understand the material provided by educators to students, whether in the form of technology or non-technology. Media is a prop that serves as a supporting tool in teaching and learning activities so that it can be obtained effectively. A medium that is commonly used at this time is internet-based blog media. The application of Blog Media that researchers apply produces results, namely the achievement of a learning room atmosphere that becomes lively and not boring. The population of this study was all students of Madrasah Aliyah Wali Songo which numbered 145 people and a sample of 20 people. This research method is a quantitative one-group experiment. The instrument used is in the form of a angket. The results of the data analysis showed that there was an increase in students' Arabic learning spirit without using blog media and using blog media in class XI MAK students. Based on the data values in the Frequencies output table, Negative Differencesa = 2 is to state the amount that produces a negative sign (-). Positive Differencesb = 17 is to state the amount that produces a positive sign (+). Tiesc = 1 is the sum that produces the zero sign (0). And total = 20 is to state the total number of signs (positive, negative or zero). While in the Test Statisticsb output table, the significant obtained is 0.001 this means 0.001 < 0.05 then Ha is accepted, and HO is rejected. With a number of learners who experienced an increase divided by the number of learners as a whole then multiplied by one hundred and the result by 85%. So, blog media influenced a number of 17 learners. This means that Media Blog has a significant effect on the spirit of learning Arabic for class XI MAK students at Madrasah Aliyah Wali Songo Sebaung Gending.